PENERAPAN KEBIJAKAN KEPALA KANTOR BPN ACEH BESAR DALAM PEMBUATAN SURAT KETERANGAN AHLI WARIS BERDASARKAN PENETAPAN MAHKAMAH SYAR’IYAH - MAYA FITRIYANDA (PREMISE LAW JURNAL, 2017)
In making Inheritance Certificate, the Head of BPN (National Land Agency) of Aceh Besar applies the policy on it by the Sharia Court’s Ruling in Aceh. Therefore, it is very interesting to be observed and analyzed. The questions are whether the process of making Inheritance Certificate for Moslems in Indonesia needs legal basis judicially, why the Head of BPN of Aceh Besar who applies the policy on making Inheritance Certificate is based on the Sharia Court’s Ruling, and what inhibiting factor in the Sharia Court in making Inheritance Certificate in Aceh Besar.This research was expected to be able to find any law on the making of Inheritance Certificate from normative, philosophical, and sociological aspects for the knowledge of law in Aceh Besar in particular. Keyword : Inheritance Certificate, Land Office of Aceh Besar